2013
DOI: 10.1080/19440049.2013.810347
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic aromatic hydrocarbons in milk powders marketed in Argentina and Brazil

Abstract: The aim of this study was to quantify polycyclic aromatic hydrocarbon (PAH) levels in milk powder samples commercialised in Argentina and Brazil during 2012. Thirty-one samples were available from the retail market. An HPLC method for the determination of PAHs was applied involving a clean-up step with silica cartridges. Recoveries were greater than 79% for all PAHs analysed. Reproducible determination with adequate detection and quantification limits (LOD and LOQ) were attained by HPLC with fluorescence detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 13 publications
1
4
1
Order By: Relevance
“…All the samples were below the regulatory limit for BaP, but 65% of commercial milk powders do not comply with the European Union limit for PAH4 [23]; the results indicated the contamination level of PAHs in the baby food. As for this study, PAH4 showed a relatively low level compared with products in other markets [6,22]. In addition, the positive detection rates of the PAH4 markers in infant formula powders, CHR, BbFA, BaA, and BaP, were 70.0%, 63.3%, 50.0%, and 23.3%, respectively.…”
Section: Sample Analysissupporting
confidence: 45%
See 1 more Smart Citation
“…All the samples were below the regulatory limit for BaP, but 65% of commercial milk powders do not comply with the European Union limit for PAH4 [23]; the results indicated the contamination level of PAHs in the baby food. As for this study, PAH4 showed a relatively low level compared with products in other markets [6,22]. In addition, the positive detection rates of the PAH4 markers in infant formula powders, CHR, BbFA, BaA, and BaP, were 70.0%, 63.3%, 50.0%, and 23.3%, respectively.…”
Section: Sample Analysissupporting
confidence: 45%
“…e extraction of PAHs in infant formula powders includes direct saponification [1,2,23], solvent extraction [22,25,26], and dispersive solid phase extraction, and a simplified version of conventional method named the quick, easy, cheap, effective, rugged, and safe (QuEChERS) extraction method has been used for the multiresidue analysis. e analytical method for the determination of the US EPA priority pollutant of 16 PAHs in edible oils was developed by an isotope dilution GC-MS method [27], which is a reference for this study, and all parameters are listed in Figure 1.…”
Section: Extraction and Purificationmentioning
confidence: 99%
“…The range of concentrations used was selected on the basis of dairy milk contamination levels reported for PCB126 (0-543 pg/g fat) (Esposito et al, 2009;TurrioBaldassarri et al, 2009) and B[a]P (0-0.28 mg/Kg dry mass) (Garcia Londoño et al, 2013;Girelli et al, 2014;Naccari et al, 2011). Fig.…”
Section: Different Modulation Of Ahr Target Genes By Selected Ligandsmentioning
confidence: 99%
“…The second one, PCB77, was selected to estimate the modulation of the pathway by a non-ortho congener displaying different receptor affinity, being characerized by a TEF value lower by a factor of thousand (Van den Berg et al, 2006). Finally, b-naphtophlavone (b-NAF) and B[a]P, a compound normally used as guideline value for PAHs contamination in milk due to its high toxicity (Garcia Londoño et al, 2013), were selected as model non DL-ligands.…”
Section: Introductionmentioning
confidence: 99%
“…2 These compounds are semi-volatile and, consequently, they are present in the atmosphere as gaseous phase and adsorbed in atmospheric particles. In water samples, the concentration of organic pollutants is found at the μg L -1 level due to their low solubility, 3,4 being their most important sources pollution, such as oil spills or wood preservative pollutants.…”
Section: Introductionmentioning
confidence: 99%